Gastric pH and Fusobacterium gastrosuis detection in relation to gastric lesions in fattening pigs - Krepelková, Z.; Karaffová, V.; Bárdová, K.; Zigo, F.; Novotný, J. (Polish Journal of Veterinary Sciences, 2026)
The development of gastric ulcers in fattening pigs is a multifactorial process influenced by gastric acidity and bacterial colonization. The aim of this study was to investigate the relationship between gastric pH and the presence of Fusobacterium gastrosuis in different regions of the stomach in relation to ulcer formation. Gastric pH in the pars oesophagea was measured in 112 fattening pigs and showed a negative correlation with lesion severity. Qualitative real-time PCR detected F. gastrosuis in 70% of samples from the glandular region and in 50% of pars oesophagea samples, with detection based on the 16S rRNA gene being more sensitive than gyrB. Although ulcers occurred predominantly in the pars oesophagea, colonization by F. gastrosuis was more pronounced in the glandular region of the stomach, suggesting that the bacterium may act as an opportunistic pathogen and, in combination with low gastric pH, indirectly contribute to mucosal damage. These findings support the hypothesis of a multifactorial pathogenesis of gastric ulcers in pigs and highlight the importance of combined monitoring of gastric pH and bacterial colonization in ulcer prevention.